DOI: 10.5353/th_b3619949
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory properties of polysaccharopeptide derived from Coriolus versicolor and its combined effect with Cyclosporine a in activated human T-cells

Abstract: Objectives  Lymphocyte homoeostasis is essential in inflammatory and autoimmune diseases. In search of natural fungal metabolites with effects on lymphocyte homoeostasis, we recently reported that polysaccharopeptide (PSP) from Coriolus versicolor exhibited ciclosporin‐like activity in controlling aberrant lymphocyte activation. This object of this study was to investigate its effect on lymphocyte homoeostasis. This was done by investigating the mechanistic actions of PSP in relation to ciclosporin by performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Obviously, effects on the ODC and c‐Myc as well as TGF‐ β are important to maintain the continuity of the surface epithelium and rapidly restore it after destruction. Many natural products are known to possess multiple bioactivities [16–21] . We suppose the polysaccharides from Ganoderma lucidum (Gl ‐ PS), which are natural products with multiple actions, may possess the activity to improve the restoration of the continuity of the surface epithelium after destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, effects on the ODC and c‐Myc as well as TGF‐ β are important to maintain the continuity of the surface epithelium and rapidly restore it after destruction. Many natural products are known to possess multiple bioactivities [16–21] . We suppose the polysaccharides from Ganoderma lucidum (Gl ‐ PS), which are natural products with multiple actions, may possess the activity to improve the restoration of the continuity of the surface epithelium after destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Coriolus versicolor (CV), which belongs to the basidiomycete family, has been a well‐known traditional food and medicinal mushroom for thousands of years. Previous studies have found that CV has antitumor, antioxidant, antibacterial, and immunomodulatory effects on various conditions (Chang et al, ; Fritz et al, ; Lee, Jiang, Sit, Yang, & Wan, ; Saleh, Rashedi, & Keating, ). Recently, CV extract was reported to have efficient hypoglycemic effects.…”
Section: Introductionmentioning
confidence: 98%
“…Krast (Ganodermataceae), a well‐known medicinal mushroom widely used for centuries in China to promote longevity and improve vigour without significant adverse effects [3,4] . As with many natural products with immunomodulatory and antitumour effects, [5–9] Gl ‐PS has been extensively studied in recent decades and demonstrated to have various biological activities, including immunomodulatory and antitumour effects [10] . The immunomodulatory and antitumour effects of Gl ‐PS include: enhancement of cytokine production as well as dendritic cell maturation and function, [11] improvement in cytokine‐induced killer cell function, [12] augmentation of cytotoxic T lymphocyte (CTL) function, [13] promotion of B16F10 cells to activate lymphocytes, [14] and inhibition of the growth of vascular endothelial cells and inhibition of the induction of vascular endothelial growth factor (VEGF) in human lung cancer cell [15] .…”
Section: Introductionmentioning
confidence: 99%